A Dawson-like clustering of human mitochondrial DNA sequences based on protein coding region - Soares, Inês (2019)
In the present paper, our main goal is focused in developing fast algorithms for human mtDNA sequence analyses, requiring minimum and explicit assumptions on mutation models and evolutionary pathways. We propose a new approach based on a construction of Dawson, a technique based on the ordering of the variable sites. In this approach, the first step corresponds to the computation of the order of the positions according to their capacity to separate the sequences into dichotomous groups. Aiming to avoid or at least to minimize the consideration of ambiguous evolutionary events such as insertions/deletions and recurrence, which cause well-known alignment problems, in the present study we only work with the protein coding sequence, the clearly more stable region in human mitochondrial genomes. This method was tested in a small set of 99 human mtDNA comprising representatives of all major haplogroups. The developed approach showed to be a choice to automate the clustering of human mtDNA sequences into broad groups, the output being in agreement with the canonical classification into macro-haplogroups deposited in the Phylotree database.